Loss aversion and mental accounting: The favorite-longshot bias in parimutuel betting - Jianying Qiu (University of Innsbruck, Department of Public Finance, 2009)
In this paper it is shown that the combination of mental accounting and loss aversion can fundamentally changes people's way of evaluating risky alternatives. The observation is applied in a market setting: Parimutuel betting markets. In parimutuel betting markets it has been found that for horses with lowest odds (favorites), market estimates of winning probabilities are smaller than objective winning probabilities; for horses with highest odds (longshot) the opposite is observed (the favorite-longshot bias). I build a game theoretical model and show that the favorite-longshot bias is the equilibrium play of the players with loss aversion, and that the degree of the favorite-longshot bias depends on the mental accounting process the players use.
Keywords: C72; D40; D81; G10; 330; loss aversion; mental accounting; parimutuel betting; the favorite-longshot bias.; Verlust; Risikoaversion; Glücksspiel; Prospect Theory; Bias; Nichtkooperatives Spiel; Theorie